Explaining Students Revisit Intention via Scarcity Cues and Perceived Value: the Role of Sensory Brand Experience as Boundary Condition - Thalib, Supriadi; Wulandjani, Harimurti; Nawasiah, Nana; Hendryadi, Hendryadi; Mais, Rimi Gusliana (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 17 Nomor 1 Tahun 2023DO - 10.24843/MATRIK:JMBK.2023.v17.i01.p01, 2023)
In response to an empirical study on scarcity cues in COVID-19, the present study offers a model of the relationship between scarcity cues and revisit intention by integrating perceived value and sensory brand experiences (SBE). The moderation mediation model (MOD MED) was tested using 426 respondents who were university students in Jakarta. The results of the analysis show that scarcity cues have a negative impact on perceived value and revisit intention. The process model has been confirmed through the role of perceived value in the scarcity cues relationship. SBE in this study has an essential role as a bearing for the negative effect of scarcity cues on perceived value and revisit intention. Hence, this study offers a theoretical contribution to the proposed model and a practical one regarding the effectiveness of "scarcity cues" marketing strategies. Keyword : Scarcity Cues, Sensory Brand Experiences, Perceived Value, Revisit Intention